SOCIAL PEDAGOGY AND PREVENTIVE WORK IN THE COMMUNITY - LEINO Mare (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
In October 2022 the society of Estonia was shocked because of aggressive girls: in a small town during one week two separate cases created scandals. A group of teenagers (14 y.) girls beats/thrashed one 12 y. girl. The boys recorded it and put the film on the web. In many newspapers and TV/ Radio shows those evidences were discussed intensively. The main question was that what is wrong with society, with families, with schools and with girls. Aggressive behaviour used to be the style of masculinity – so, the brutality of the girls was especially hard to understand, at least according to comments in media. The research method here is a content analysis of media in Estonia, during October/November 2022 – starting from those aggressive episodes. The aim of the article is to find out social pedagogical messages for possible prevention in the future. Proactive behaviour helps to make communities safer.